2021
DOI: 10.5005/jp-journals-10071-23748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Non-neutropenic Patients with Invasive Candidiasis: A Retrospective Study in a Tertiary Care Center

Abstract: A bstract Introduction: Invasive candidiasis (IC) is a major cause of morbidity and mortality in critically ill patients in the intensive care unit (ICU). In this study, we aim to analyze the clinical profile, species distribution, and susceptibility pattern of patients with IC. Methods: Case records of non-neutropenic patients ≥18 years of age with IC between January 2016 and June 2019 at a tertiary care referral hospital were analyzed. IC was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
1
1
Order By: Relevance
“…Sahni et al also carried out a study on candidemia in New Delhi and reported an incidence of 6.9 % [14]. The prevalence rate of C. albicans in this study is 28.57 % among all species, a figure notably lower than reported in other studies [15][16][17]. Among NCAs, C. tropicalis stands out as the major causative species of Candidemia, consistent with findings in various studies [1,9,11,15,[18][19][20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sahni et al also carried out a study on candidemia in New Delhi and reported an incidence of 6.9 % [14]. The prevalence rate of C. albicans in this study is 28.57 % among all species, a figure notably lower than reported in other studies [15][16][17]. Among NCAs, C. tropicalis stands out as the major causative species of Candidemia, consistent with findings in various studies [1,9,11,15,[18][19][20].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence rate of C. albicans in this study is 28.57 % among all species, a figure notably lower than reported in other studies [15][16][17]. Among NCAs, C. tropicalis stands out as the major causative species of Candidemia, consistent with findings in various studies [1,9,11,15,[18][19][20]. Another significant causative organism identified in this study was C. parapsilosis, an opportunistic pathogen associated with candidemia, consistent with findings from various other studies [11,[21][22][23].…”
Section: Discussioncontrasting
confidence: 87%
“…For example, Sridharan et al aimed to analyze the clinical profile, species distribution, and susceptibility pattern of patients with invasive candidiasis. 3 They used descriptive statistics to express the characteristics of their study sample, including mean (and standard deviation) for normally distributed data, median (with interquartile range) for skewed data, and percentages for categorical data.…”
Section: W Hat Is the R Esearch H Ypothesis ?mentioning
confidence: 99%